1977
DOI: 10.1530/jrf.0.0500129
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an inhibin-like factor present in bovine and porcine follicular fluid on gonadotrophin levels in ovariectomized rats

Abstract: De Jong & Sharpe (1976) recently observed that bovine follicular fluid from which steroids had been removed reduced peripheral levels of FSH but not of LH when injected into newly castrated male rats. The effect was ascribed to a factor resembling testicular inhibin. In the present report, observations were extended to the effects of this inhibin-like factor on FSH and LH levels in female rats. Attention has also been paid to the question of whether the factor is present in species other than the cow and wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0
1

Year Published

1979
1979
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(42 citation statements)
references
References 9 publications
4
37
0
1
Order By: Relevance
“…Recently, such an inhibin-like or gonadostatin activity from ovarian follicular fluid has been reported (33)(34)(35)(36)(37)(38). However, stimulatory effects of follicular fluid on the pituitary secretion of gonadotropin have never before been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, such an inhibin-like or gonadostatin activity from ovarian follicular fluid has been reported (33)(34)(35)(36)(37)(38). However, stimulatory effects of follicular fluid on the pituitary secretion of gonadotropin have never before been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Steroid free bovine (de Jong, Welschen, Hermans, Smith & van der Molen, 1978), equine (Miller, Wesson & Ginther, 1979), human (Chappel, Holt & Spies, 1980), monkey (Channing, Anderson & Hodgen, 1980) and porcine (de Paolo, Wise, Anderson, Barraclough & Channing, 1979b;Schänder, Anderson, Barraclough & Channing, 1980) (1978) indicated that granulosa cells are the probable source of this follicular inhibin, while studies of the rat (de Paolo, Shander, Wise, Barraclough & Channing, 1979a) and monkey (Channing et ai, 1980) have shown that inhibin is secreted into the ovarian vein, thus strengthening the concept that ovarian inhibin may be physiologically important in the regulation of FSH secretion. Inhibin activity in follicular fluid is related to follicle size (Welschen, Hermans, Dullart & de Jong, 1977) and ovarian inhibin production changes throughout the oestrous/menstrual cycle (de Paolo et ai, 1979a;Chappel et ai, 1980). However, there is little information about the regulation of ovarian inhibin production.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, rather that regressing, the dominant follicle had an extended lifespan. Thus, the suppressive effect of inhibin and other follicular products that would be produced by the persistent follicle may account for the unchanged FSH levels reported herein [115,155,168,[176][177][178].…”
Section: Discussionmentioning
confidence: 79%